Sakit Belakang :Satu kajian kesan aplikasi mekanik badan dalam kalangan pelajar kejururawatan di Hospital Universiti Sains Malaysia (HUSM) - Izhadaini Madiah, Mohamad (PPSP, Universiti Sains Malaysia, 2007)
Back pain is defined as an episode of uncomfortable feeling at the backbone area and spinal chord which can affect daily activities of a person. The back area is started from scapula to border line below waist. Pathological symptom or pain are like cramp for more than one day at the back which includes muscles, tendon, joints and intervertebral disc. The body mechanic can be defined as a method of using body parts effectively and safely during activities done. It is very important especially for the health professionals such as nurses and is being taught and implemented during learning to be a nurse so that the proper use of body mechanic can be applied during practical in ward to avoid back pain when they started to be a nurse later. The research which is to be done is to determined whether nursing students use the right body mechanic as they learned during practical in HUSM. This research is important among nursing student to avoid problems during practical in ward. Learning of body mechanic is important for nurses so that they can use it to maintain body balancing,ease their work,reduce tiredness and also to reduce the risk of the tension of muscle, joints and tendon. However there are some factors that make them do not apply the right body mechanic such as not enough time and lazy to do that. This descriptive research had been done using verified questionnaires forms. These forms assist of part A which is for demography data, part B questionnaires about the knowledge level, part C questionnaires of the level of the pain and part D for the usage of body mechanic among students during practical in HUSM. An observation had been done to 30 forth year students who are doing degree in nursing in USMKK. Another student involve are 2nd year student from nursing college of UDM consist of 19 students and 26 students from third year. All respondents had learnt about body mechanic. All their knowledge about body mechanic, the application during practical and back pain problem among nursing student had been analysed using SPSS. This research is to encourage nursing student to apply body mechanic not only during learning at college but also during working in the future. This could reduce the risk of body pain among nursing professionals. It also to create students altitude to pay attention to self health in order to give proper treatment to patient. If the nurse get the body pain, it would affect their working performance. Comprehensive courses are very important to upgrade knowledge among nurses.